Postpositive Attribute Distributors of the Categories of Professional Leader in the Russian Practice (Proceedings of Southern Federal University. Philology, 2018)
Marina A. Solovyova (Vladimir, Russian Federation)The dynamism of changes of lexical system receives reflection in the sphere of compatibility of units, in particular the nominations of persons on professional accessory, a position, a military rank. The specified nominations have semantic duality, that is called the person and give information on professional activity, experience, qualification, estimate the status in collective, society from a position of the labor relations. The group of the nominations of persons by profession is actively developing that causes relevance of studying of combinatory opportunities of the entered nouns with various uncoordinated and coordinated post-positive definitions in Russian of the 21st century.Systematization of collected material reflects syntagmatic opportunities of the 140 most met word forms of nouns of the professional figure which act as basic words in the compound nominations. Basic words function in phrases of various syntactic structure, it is about the two-word, threeword and multicomponent nominations of people. The language base of a research includes 1040 contexts. Productive models of the use of attributive distributors from the point of view of lexical meanings which have allowed to make classification of distributors by structural-semantic groups are allocated.Key words: attributive distributors, lexical compatibility, uncoordinated definitions, nominations of the professional figure, postposition, difficult phrases, compound names.DOI 10.23683/1995-0640-2018-1-93-102